Are children with SARS‐CoV‐2 infection at high risk for thrombosis? Viscoelastic testing and coagulation profiles in a case series of pediatric patients. Issue 12 (24th October 2020) - Al‐Ghafry, Maha; Aygun, Banu; Appiah‐Kubi, Abena; Vlachos, Adrianna; Ostovar, Gholamabbas; Capone, Christine; Sweberg, Tod; Palumbo, Nancy; Goenka, Pratichi; Wolfe, Lawrence C.; Lipton, Jeffrey M.; Acharya, Suchitra S.
Abstract: The coagulopathy of the novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is well documented in adults, with increases in D‐dimer and prothrombin time found to be strong predictors of mortality, and anticoagulation shown to decrease this mortality. Viscoelastic parameters such as elevations in maximum clot firmness (MCF) on rotational thromboelastometry (ROTEM) have correlated with a hypercoagulable state in adults with SARS‐CoV‐2. We report our experience in children infected with SARS‐CoV‐2, with noted elevations in D‐dimer and MCF on ROTEM (indicating hypercoagulability). Exploration of viscoelastic testing to provide additional laboratory‐based evidence for pediatric‐specific risk assessment for thromboprophylaxis in SARS‐CoV‐2 is warranted.